Acute Interstitial Pneumonia (Hamman-Rich Syndrome) as a Cause of Idiopathic Acute Respiratory Distress Syndrome. (29th May 2011) - Bruminhent, Jackrapong; Yassir, Shahla; Pippim, James
Abstract : Hamman-Rich syndrome, also known as acute interstitial pneumonia, is a rare and fulminant form of idiopathic interstitial lung disease. It should be considered as a cause of idiopathic acute respiratory distress syndrome. Confirmatory diagnosis requires demonstration of diffuse alveolar damage on lung histopathology. The main treatment is supportive care. It is not clear if glucocorticoid therapy is effective in acute interstitial pneumonia. We report the case of a 77-year-old woman without pre-existing lung disease who initially presented with mild upper respiratory tract infection and then progressed to rapid onset of hypoxic respiratory failure similar to acute respiratory distress syndrome with unknown etiology. Despite glucocorticoid therapy, she did not achieve remission and expired after 35 days of hospitalization. The diagnosis of acute interstitial pneumonia was supported by the histopathologic findings on her lung biopsy.